Episodic dural stimulation in awake rats: A model for recurrent headache - Michael L. Oshinsky (2018)
Objectives. - To model, in rats, the development of chronic trigeminal nociceptive hypersensitivity seen in patients with recurrent headache. Background. - Pathophysiology studies suggest that patients with recurrent migraine headache experience repeated bouts of dural nociceptor activation. In some patients, the severity and frequency of headache attacks increase over time. Patients with recurrent headache are hypersensitive to nitric oxide donors, such as glyceryl trinitrate (GTN). Current trigeminal pain models do not reflect the repeated episodic nature of dural nociceptor activation in patients with recurrent headache. Repeated nociceptor activation creates long-lasting changes in the periphery and brain due to activity-dependent neuronal plasticity. An animal model of repeated activation of dural nociceptors will facilitate the study of the physiological changes caused by repeated, episodic pain and the factors important for the transition of episodic to chronic migraine. Methods. - We induced dural inflammation by infusing an inflammatory soup (IS) through a cannula on the dura in awake behaving rats. This was repeated 3 times per week for up to 4 weeks. Periorbital pressure sensory testing was used to monitor the change in trigeminal sensitivity. Rats were challenged with GTN to test the hypothesis that many dural stimulations are required to model the hypersensitivity of migraine patients. Quantitative trigeminal sensory testing and microdialysis in the trigeminal nucleus caudalis (TNC) were used to measure GTN hypersensitivity. Results. - Multiple infusions of IS (>8), over weeks, induced a long-lasting decrease in periorbital pressure thresholds that lasted >3 weeks after the last infusion. In contrast, IS infusion in IS-naive rats and those that received 3 IS infusions produced only short-lasting decreases in periorbital pressure thresholds. Rats that received more than 8 IS infusions showed a marked increase in their neurochemical and behavioral responses to GTN. In these rats, GTN induced a decrease in periorbital von Frey thresholds that lasted >5 hours. In contrast, in rats that received only 3 IS infusions, GTN caused a threshold decrease for 1.5 hour. In vivo microdialysis in the TNC showed that GTN increased extracellular glutamate levels in rats with more than 8 IS infusions to 7.7 times the basal levels. In IS-naive rats and those that received only 3 IS infusions, the extracellular glutamate levels rose to only 1.7 and 1.9 times the basal level, respectively. Conclusions. - Repeated IS stimulation of the dura produces a chronic state of trigeminal hypersensitivity and potentiates the response to GTN. This hyperresponsiveness outlasts the last IS infusion and is the basis of our rat model of recurrent headache. This model can be used to study the changes in the brain and periphery induced by repeated trigeminovascular nociceptor activation and has the potential to elucidate the mechanisms for the transition of episodic to chronic headache. © 2007 the Authors.